Association between life satisfaction and oral health conditions at adolescents in urban and rural areas in Indonesia: pilot pathfinder survey - Fuad Husain Akbar (Makassar Dental Journal, 2020)
Tujuan : Tuju a nObjective: To determine the association between life satisfaction and oral health conditions at adolescents in rural and urban areas. Method: A pilot pathfinder survey was conducted on April 9-14th 2018 using qSurvei ini menggunakan kuisioner.uestionnaires. The samples were 416 adolescents aged 11-14 in urban and rural areas of Gowa regency, Indonesia. Chi-square and Pearson correlation test were carried out to test the relationship between life satisfaction and self-rated oral health condition. Hasil : Pada daerah urban, terdapat hubungan yang signifikan antara kepuasan hidup dengan tingkat kesehatan mulut (p=0.040) , penilaian pengalaman karies yang dinilai sendiri (p=040) , dan penilaian pengalaman maloklusi yang dinilai sendiri (p=0.006) .Result: In urban areas, there is a significant relationship between life satisfaction and oral health, p-value was 0.040; self-assessed caries experience, p-value was 0.040; and self-assessed malocclusion experience, p-value was 0.006. Pada daerah rural,In rural areas, terdapat hubungan yang signifikan antara kepuasan hidup dengan penilaian pengalaman maloklusi yang dinilai sendiri (p=0.002) .there is a significant relation-ship between life satisfactions with self-assessed malocclusion experience, p-value was 0.002. KesimpulanConclusion:: Kesimpulan yang didapatkan dari penelitian ini adalah terdapat hubungan antara kepuasan hidup dengan kondisi kesehatan mulut pada usia remaja di urban dan rural Kabupaten Gowa 2018.There is an association between life satisfaction and oral health conditions in adolescents in urban and rural areas.